TANGGUNG JAWAB KEJAHATAN INSIDER TRADING YANG DILAKUKAN TERHADAP PERDAGANGAN SAHAM DI PASAR MODAL (CONTOH KASUS JOUSKA INDONESIA) - Anthony Willyus Wongkar; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2022)
Insider trading is a crime in the capital market which is detrimental to the existence of the capitalmarket itself. The practice of insider trading is expressly prohibited through Republic of Indonesia’sLaw Number 8 of 1995 concerning the Capital Market which categorizes the practice of insidertrading as a crime. Insider trading is said to be a form of crime because of an unfair position intrading transactions. Insiders could gain profits and or avoid losses from trading results using theirinside information that af ects trading prices (materials information). Investors who follow anef icient market will be disadvantaged because trading has occurred before information about anissuer is published. Therefore, the law prohibits both company insiders or their partners who havebusiness relations as well as securities companies who have previously known material informationof a company to properly safeguard the information and not conduct any transactions for personalgain. In the history of insider trading in Indonesia, there has not been a single case of insidertrading that has been dragged to litigation. In the case of Jouska Finansial Indonesia, there was anallegation of insider trading practices that harmed his own clients. For these losses, it is hoped thatthe party responsible for the losses suf ered by the victims can be determined.